2020
DOI: 10.1080/1828051x.2020.1848462
|View full text |Cite
|
Sign up to set email alerts
|

Quality traits, fatty acids, mineral content of meat and blood metabolites changes of broiler chickens after artificial infection with sporulatedEimeria tenellaoocysts

Abstract: This study was to investigate physicochemical characteristics, fatty acids, minerals and hematological alterations in broiler chickens artificially infected with 1 Â 10 4 sporulated oocysts of Eimeria tenella. Results revealed that pH values were decreased (p ˂ .05) in the infected group (IG) at 7 and 9 days post infection (dpi) than those at 5 dpi, although no significant differences between the non-infected group (NIG) and IG. Infection with E. tenella did not affect meat colour parameters except that rednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Plasma enzymes are key biochemical markers of hepatic health and function and their elevation in circulation is interpreted as a sensitive indicator of liver injury ( Rivetz et al, 1977 ; Jing et al, 2014 ; Cha et al, 2020 ). The LPS challenge elevated plasma AST and GLDH and decreased GGT and lipase in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma enzymes are key biochemical markers of hepatic health and function and their elevation in circulation is interpreted as a sensitive indicator of liver injury ( Rivetz et al, 1977 ; Jing et al, 2014 ; Cha et al, 2020 ). The LPS challenge elevated plasma AST and GLDH and decreased GGT and lipase in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the effects of Eimeria infection on meat quality in broiler chickens ( Table 2 ). Eimeria infection induced lipid peroxidation in the breast meat, according to Cha et al [ 58 ] and Partovi et al [ 59 ]. Though conducted under identical experimental conditions, Qaid et al [ 60 ] reported E. tenella infection increased lightness, while Qaid et al [ 61 ] showed that E. tenella infection decreased lightness in the breast meat.…”
Section: Challenging Conditions In Broiler Production Are Associated ...mentioning
confidence: 99%